Respuesta :
change in velocity of larger moose: (1/3)v - v = -(2/3)v
change in velocity of small moose: (1/3)v - (-v) = (4/3)v
- (change in velocity of larger moose)/(change in velocity of smaller moose) = 2
Thank you for posting your question here at brainly. I hope the answer will help you. Feel free to ask more questions.
change in velocity of small moose: (1/3)v - (-v) = (4/3)v
- (change in velocity of larger moose)/(change in velocity of smaller moose) = 2
Thank you for posting your question here at brainly. I hope the answer will help you. Feel free to ask more questions.
change in velocity of larger moose: (1/3)v - v = -(2/3)v
change in velocity of small moose: (1/3)v - (-v) = (4/3)v
(change in velocity of larger moose)/(change in velocity of smaller moose) = 2
Explanation:
It is the "ma" in F=ma that we tend to call inertia.Inertia is that the resistance of any entity to any amendment in its position and state of motion.
his includes changes to the object's speed, direction, or state of rest. Inertia is additionally outlined because the tendency of objects to stay getting a line at a continuing speed.